Study of The Impact of Adding AIC on the Wear Properties of Unalloyed Steel Produced by Metallurgy Powder - Salem Khalifa Rhoma; Fathi Etaher Elbakoush; Salhain M. Salhein (Surman Journal of Science and Technology, 2025)
In the powder metallurgy method, the desired properties are produced in a more comprehensive and controlled manner compared to the casting method. Based on this reason, our study is planned to be realized by powder metallurgy method. In our study, Graphite and Aluminum Carbide (AlC) were added to the Fe matrix. AlC was added at different determined proportions. The mixtures were mixed for one and a half hours using the Turbulo device. In order to bring these mixed powders into block form, 700 MPa was applied with one-way pressing. Block samples were sintered in an argon atmosphere at 1350°C. SEM and optical microscope device were used for microstructural properties and post-abrasion examinations. (SEM microstructure, SEM EDS). Hardness and wear tests were carried out to determine the mechanical properties.